Використання відеоконтенту у стратегії соціальних мереж для залучення клієнтів автобусних перевезень - Мина, Жанна; Марковець, Марія (Видавництво Львівської політехніки, 2025)
The abstracts examine strategies for creating and distributing video content to increase brand awareness, strengthen customer loyalty, and increase sales. The article focuses on current trends in video marketing, including the popularity of short, dynamic, and authentic videos. The study emphasizes the need to adapt content strategies to changing audience preferences and effectively use social platforms to engage with customers and position the brand.
Keywords: відеоконтент; соціальні мережі; маркетинг; автобусні перевезення; просування бізнесу; цифрові комунікації; брендинг; залучення аудиторії; тренди відеомаркетингу; стратегії розповсюдження контенту